Synthesis and Dynamics of Nanosized Phenylene–Ethynylene–Butadiynylene Rotaxanes and the Role of Shape Persistence. (2nd February 2016) - Schweez, Christopher; Shushkov, Philip; Grimme, Stefan; Höger, Sigurd
Abstract: Phenylacetylene‐based [2]rotaxanes were synthesized by a covalent‐template approach by aminolysis of the corresponding prerotaxanes. The wheel and the bulky stoppers are made of phenylene–ethynylene–butadiynylene macrocycles of the same size. The stoppers are large enough to enable the synthesis and purification of the rotaxane. However, the wheel unthreads from the axle at elevated temperatures. The deslipping kinetics and the activation parameters were determined. We described theoretically the unthreading by state‐of‐the‐art DFT‐based molecular‐mechanics models and a string method for the simulation of rare events. This approach enabled us to characterize in detail the unthreading mechanism, which involves the folding of the stopper during its passage through the wheel opening, a process that defies intuitive geometrical considerations. The conformational and energetic features of the transition allowed us to infer the molecular residues controlling the disassembly timescale.